Nogle grundbegreber i Grundtvigs pædagogiske tanker - Bugge, K. E. (Grundtvig-Studier, 2008)
Nogle grundbegreber i Grundtvigs pædagogiske tanker [Some basic concepts in the educational thinking of Grundtvig] By K. E. Bugge The subject of this contribution is the study of basic concepts in Grundtvig’s educational thinking. After discussion of the methodological approach, attention is focused on two basic concepts, life and light. Finally, the importance of Grundtvig’s negative and “invisible” concepts is emphasised. “Invisible” concepts are those which are not expressly mentioned in the text, but which nevertheless through a meticulous study of his unprinted drafts are seen to have been present in his deliberations.